Impact of low‐carbohydrate diet on body composition: meta‐analysis of randomized controlled studies. (5th April 2016) - Hashimoto, Y.; Fukuda, T.; Oyabu, C.; Tanaka, M.; Asano, M.; Yamazaki, M.; Fukui, M.
Summary: The effect of low‐carbohydrate diet (LCD) on body composition, especially fat mass, in obese individuals remains to be elucidated. We performed a meta‐analysis to provide quantitative summary estimates of the mean change of body weight (kg) and fat mass (kg) in LCD comparing to those in control diet. Literature searches were performed using EMBASE, MEDLINE and Cochrane Library until Dec 2014. Fourteen randomized controlled studies were included in this meta‐analysis. Eight studies including very LCD (50 g carbohydrate or 10% calorie from carbohydrate) and seven studies including mild LCD (about 40% calorie from carbohydrate). Meta‐analysis carried out on data of 1416 obese individuals, showed that LCD was associated with decrease in body weight (−0.70 kg [95% CI −1.07/−0.33]) or fat mass (−0.77 kg [−1.55/−0.32]). Subgroup meta‐analysis of studies in over 12 months suggested that LCD was not associated with decrease in body weight (−0.44 kg [−0.94/0.07]), but LCD was associated with decrease in fat mass (−0.57 kg [−1.05/−0.09]). In addition, very LCD was associated with decrease in fat mass (−0.97 kg [−1.50/−0.44]), but mild LCD was not associated with decrease in fat mass (−0.43 kg [−1.15/0.33]). LCD, especially very LCD, might be effective for decrease in fat mass in obese individuals. © 2016 World Obesity